ANALISIS PERFORMA PRIMARY AIR HEATER (PAH) PLTU ASAM ASAM UNIT I – KALIMANTAN SELATAN - Rinto Muhaimin S; Abdul Ghofur (Universitas Lambung Mangkurat, 2019)
Power plan has an important role in the electricity supply bussiness, one of them is PLTU Asam Asam which is Unit Pelaksana Pembangkitan Asam Asam. By using fuel coal fired type, this work continously to generate maximum power in generating electricity. In terms working to have maximum power continuously in boiler, Boiler have equipment Primary Air Heater (PAH) to repairing the efficiency. To get best performance Primary Air Fan (PAH) is doing routine maintenance.The Effect is routine maintenance for repairing, abrasive and corrosive material Primary Air Fan (PAH) to be air leakage. This final project aims to know performance before and after repairing compare commissioning perform. In this final project compiling, the using methods are literature study, observation, data processing, data analyzing, and conclusion. Literature study is searching of source for reference, then the observation is done by collecting data based on the parameters required. These data are analyzed to derive conclusions from the object being observed.The result of final project research shows that different escalation occurred after repairing. This can proven by calculation and analysis of data which obtained before repairing the efficiency 68,5% and work 68,6%, and Air leakage reduce 83,18%% and work 70,55%. Keywords: Efficiency, Performance, Boiler, Heat Loss Method